Multiple Ornaments—Multiple Signaling Functions? The Importance of Song and UV Plumage Coloration in Female Superb Fairy-wrens (Malurus cyaneus) - Mahr, Katharina; Evans, Christine; Thonhauser, Kerstin E.; Griggio, Matteo; Hoi, Herbert (Frontiers in Ecology and Evolution, 2016)
Showy ornaments are considered as outcomes of sexual selection processes. They provide a “badge of status” to impress conspecific rivals or potential mating partners. Single ornaments may signal attractiveness or individual quality, yet many species display multiple ornaments. There are several hypotheses that explain the existence of multiple ornaments, suggesting that different ornaments serve as different information sources. They may provide either additive or redundant information on the same quality traits, or are simply evolutionary leftovers with no further relevant information. Although females of many species display elaborated traits, most studies regarding multiple ornaments focus on males. However, given that in many species females also display multiple ornaments, the question about their functional significance arises. To understand the existence of female multiple ornaments we investigated ornamental features of female Superb Fairy-wrens (Malurus cyaneus), focusing on song and variation in plumage characteristics. Female Superb Fairy-wrens produce complex solo songs, for territorial defense, and have bright blue tail feathers. We examined the relationships between song and plumage coloration characteristics in relation to female quality parameters to investigate whether, and to what extent existing hypotheses on multiple ornaments in males may also apply to females. Based on song recordings and spectrometric measurements of UV-coloration of tail feathers, we derived a series of different song and plumage parameters. Our results indicate interrelationships between the song length (total number of elements in female song) and female body size, but not UV-coloration. Interestingly, song complexity (number of different elements in female song) did not correlate with morphological parameters, UV-Chroma and song length respectively. This suggests that i) song and plumage characteristics evolved independently and ii) even within one trait, namely song, multiple signalling should be considered. To our knowledge, this is the first study investigating multiple traits in female songbirds, raising the idea that multiple signalling of sexually selected traits is not restricted to males only.